Understanding Complex Tribofilms by Means of H3BO3-B2O3 Model Glasses - Spadaro, F; Rossi, A; Ramakrishna, Shivaprakash N; Lainé, E; Woodward, P; Spencer, N D (Langmuir, 2018)
The discovery of the spontaneous reaction of boric oxides with moisture in the air to form lubricious H3BO3 films has led to great interest in the tribology of boron compounds in general. Despite this, a study of the growth kinetics of H3BO3 on a B2O3 substrate under controlled relative humidity (RH) has not yet been reported in the literature. Here, we describe the tribological properties of H3BO3-B2O3 glass systems after aging under controlled RH over different lengths of time. A series of tribological tests has been performed applying a normal load of 15 N, at both room temperature and 100 °C in YUBASE 4 oil. In addition, the cause of H3BO3 film failure under high-pressure and high-temperature conditions has been studied to find out whether the temperature, the tribostress, or both influence the removal of the lubricious film from the contact points. The following techniques were exploited: confocal Raman spectroscopy to characterize the structure and chemical nature of the glass systems, environmental scanning electron microscopy to examine the morphology of the H3BO3 films developed, atomic force microscopy to monitor changes in roughness as a consequence of the air exposure, focused-ion-beam scanning electron microscopy to measure the average thickness of the H3BO3 films grown over various times on B2O3 glass substrates and to reveal the morphology of the sample in the vertical section, tribological tests to shed light on the system's lubricating properties, and finally small-area X-ray photoelectron spectroscopy to investigate the composition of the transfer film formed on the steel ball while tribotesting.The discovery of the spontaneous reaction of boric oxides with moisture in the air to form lubricious H3BO3 films has led to great interest in the tribology of boron compounds in general. Despite this, a study of the growth kinetics of H3BO3 on a B2O3 substrate under controlled relative humidity (RH) has not yet been reported in the literature. Here, we describe the tribological properties of H3BO3-B2O3 glass systems after aging under controlled RH over different lengths of time. A series of tribological tests has been performed applying a normal load of 15 N, at both room temperature and 100 °C in YUBASE 4 oil. In addition, the cause of H3BO3 film failure under high-pressure and high-temperature conditions has been studied to find out whether the temperature, the tribostress, or both influence the removal of the lubricious film from the contact points. The following techniques were exploited: confocal Raman spectroscopy to characterize the structure and chemical nature of the glass systems, environmental scanning electron microscopy to examine the morphology of the H3BO3 films developed, atomic force microscopy to monitor changes in roughness as a consequence of the air exposure, focused-ion-beam scanning electron microscopy to measure the average thickness of the H3BO3 films grown over various times on B2O3 glass substrates and to reveal the morphology of the sample in the vertical section, tribological tests to shed light on the system's lubricating properties, and finally small-area X-ray photoelectron spectroscopy to investigate the composition of the transfer film formed on the steel ball while tribotesting.